САМОРЕГУЛЯЦІЯ ЯК МЕХАНІЗМ ФОРМУВАННЯ ПРОФЕСІЙНОЇ НАДІЙНОСТІ МАЙБУТНІХ ФАХІВЦІВ З АВАРІЙНОГО ОБСЛУГОВУВАННЯ ТА БЕЗПЕКИ НА АВІАЦІЙНОМУ ТРАНСПОРТІ - Лещенко, Геннадій (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті зроблено спробу проаналізувати роль саморегуляції у формуванні професійної надійності майбутніх фахівців з аварійного обслуговування та безпеки на авіаційному транспорті. Встановлено, що саморегуляція є одним із провідних механізмів забезпечення професійної надійності фахівців екстремального профілю. Теоретично обґрунтовано та практично доведено ефективність психофізіологічних методів формування саморегуляції курсантів (аутогенне тренування, ідеомоторне тренування, вольова регуляція ритму дихання). В статье сделана попытка проанализировать роль саморегуляции в формировании профессиональной надежности будущих специалистов по аварийному обслуживанию и безопасности на авиационном транспорте. Установлено, что саморегуляция является одним из ведущих механизмов обеспечения профессиональной надежности специалистов экстремального профиля. Теоретически обосновано и практически доказана эффективность психофизиологических методов формирования саморегуляции курсантов (аутогенная тренировка, идеомоторная тренировки, волевая регуляция ритма дыхания). Ther’s been made an attempt to analyze the role of self-regulation in the process of the formation of professional reliability of future specialists of aviation emergency service and safety. It’s been found out there is no single understanding of self-regulation of human activity in phylosophy, pedagogy and psychology which makes it difficult to study the mentioned problem. It’s been offered to define the abillity of self-regulation while learning activity as the student’s feature to control his activity while learning, improve his knowledge, skills and abilities. It’s been stated that self-regulation is one of the leading mechanisms to provide the specialist’s professional reliability trained for the extreme situations. The effectiveness of psycho-physiological methods in the formation of student’s self-regulation is theoretically and practically grounded (autogenic training, ideomotor training, volitional regulation of the rhythm of breath).